Faulty Adaptation to Repeated Face-Name Associative Pairs in Mild Cognitive Impairment is Predictive of Cognitive Decline. (26th June 2017) - Jurick, Sarah M; Weissberger, Gali H; Clark, Lindsay R; Wierenga, Christina E; Chang, Yu-Ling; Schiehser, Dawn M; Han, S Duke; Jak, Amy J; Dev, Sheena I; Bondi, Mark W
Abstract: Objective: We examined BOLD (Blood-Oxygen-Level Dependent) activity reduction upon stimuli repetition of face-name pairs in older adults with amnestic (aMCI) and non-amnestic (naMCI) mild cognitive impairment diagnosed using a comprehensive actuarial method, and relationships between activity reduction and behavioral indices. Method: Twenty-nine cognitively healthy older adults (CHs) and 20 with MCI ( n = 12 aMCI; n = 8 naMCI) underwent functional MRI event-related imaging, a comprehensive neuropsychological battery, and 1-year follow-up exam. During scanning, participants were shown face-name pairs 1–3 times and administered a post-scan recognition task. Results: The MCI group demonstrated less activity reduction upon repetition of face-name pairs within the MTL and other regions compared to CHs. Less activity reduction was associated with poorer Time 1 neuropsychological performance for the CH group and poorer post-scan recognition performance for the MCI group. Less activity reduction was related to poorer neuropsychological performance at Time 2 in the MCI group. Within MCIs, those with aMCI demonstrated less activity reduction upon repetition of face-name pairs than those with naMCI. Conclusions: Distinct patterns of brain activity were identified in the MCI group compared to CHs, and aMCI compared to naMCI. Activated regions were not restricted to traditional memory circuitry, implicating a wider network of regions involved in the encoding of associative tasks. Findings add support to the hypothesis that lack of reduced BOLD activity reflects "faulty adaptation" to repeated stimuli and that reduction in activity represents successful encoding processes. They also provide further support for use of the face-name paradigm as a marker of prodromal Alzheimer's disease, and method to distinguish between MCI subtypes.